Pamer Kemewahan: Kajian Teori Konsumsi Thorstein Veblen - Indra Setia Bakti; Anismar Anismar; Khairul Amin (Sociology Department Of Syiah Kuala University, 2020)
This article aims to discuss Thorstein Veblen's perspective about the behavior of waste or excessive consumption by the leisure class. This article uses the library research to understanding the perspective of Veblen's theory of consumption. We review Veblen's work, The Theory of the Leisure Class, as the main note complemented by relevant books and journals to support this study. The leisure class in this regard act deliberately to display their wealth. The newly rich group flaunted the luxury of their life with a motive to accommodate their desire for social respect and social status. The leisure class realizes their social actions through conspicuous leisure time consumption and conspicuous consumption of goods characterized by imitative and emulative behavior among the actors involved in it. The conspicuous consumption behavior produces élite taste which in turn has a social impact that affects the class behavior of the lower strata.AbstrakArtikel ini bertujuan untuk mendiskusikan sudut pandang Thorstein Veblen dalam melihat perilaku konsumsi berlebihan yang dilakukan oleh kelas sosial tertentu dalam masyarakat. Studi ini menggunakan metode kajian pustaka dalam memahami perspektif teori konsumsi Veblen. Data dalam artikel ini bersumber dari karya-larya Veblen sendiri, The Theory of the Leisure Class, serta buku-buku dan jurnal-jurnal yang relevan dalam mendukung artikel ini. Perilaku ini rupanya lahir dari sebuah konteks sosial dimana kelompok orang kaya baru mencoba mengakomodasi hasrat mereka akan penghargaan sosial dan status sosial. Hal ini diwujudkan melalui konsumsi waktu luang mencolok dan konsumsi barang mencolok yang ditandai dengan perilaku imitatif dan emulatif diantara aktor-aktor yang terlibat di dalamnya. Perilaku konsumsi mencolok menghasilkan selera elite yang selanjutnya meluas dan berdampak secara sosial dimana mempengaruhi perilaku kelas dari strata yang lebih rendah